The informational universe of Allah: an Islamic perspective on quantum information theory - David Leong; M Abu Saleh (Penerbit Universiti Kebangsaan Malaysia, 2024)
This scholarly inquiry initiates a nuanced exploration into the Islamic conceptualization of Allah as ‘Al-`Alim (the All-Knowing) and ‘Al-Khabir’ (the All-Aware), postulating a reconciliation wherein Allah is identified as the quintessential Intelligence and truth. Allah’s attributes of divine omniscience and ubiquitous awareness underscore a divine understanding enveloping all of existence, positioning Him as the epitome of All Information. This paper delves into the intersection of Islamic theological constructs and modern information theory, proposing a novel interpretation that aligns Allah’s divine omniscience with the theory's principles. Information theory posits that the foundation of all information is inherently probabilistic, mirroring the probabilistic outcomes observed in quantum mechanics. This seemingly contradicts ‘Al-Qadar’, an All-Knowing Allah's predetermined will or predestination. However, we can bridge this gap by considering Allah as the embodiment of all information. This paper facilitates a richer understanding of Allah’s predetermined will in Islam and builds bridges with the randomness and unpredictable nature witnessed in the quantum world. This research aims to augment Allah as the Infinite Information through an interdisciplinary lens, bridging quantum indeterminacy and Islamic Omnipotence. This quantum-religious interface reconciles quantum information theory with Islamic theological constructs